Effect of Nonsmooth Nose Surface of the Projectile on Penetration Using DEM Simulation. (21st November 2017) - Han, Jing; Li, Dong; Wang, Wenhao; Chen, Zhigang
Abstract : The nonsmooth body surface of the reptile in nature plays an important role in reduction of resistance and friction when it lives in a soil environment. To consider whether it was feasible for improving the performance of penetrating projectile we investigated the influence of the convex as one of nonsmooth surfaces for the nose of projectile. A numerical simulation study of the projectile against the concrete target was developed based on the discrete element method (DEM). The results show that the convex nose surface of the projectile is beneficial for reducing the penetration resistance greatly, which is also validated by the experiments. Compared to the traditional smooth nose structure, the main reason of difference is due to the local contact normal pressure, which increases dramatically due to the abrupt change of curvature caused by the convex at the same condition. Accordingly, the broken particles of the concrete target obtain more kinetic energy and their average radial flow velocities will drastically increase simultaneously, which is in favor of decreasing the interface friction and the compaction density of concrete target around the nose of projectile.